(untitled) (Baghdad Science Journal, 2004)
The corcosion behoviour of Aluminum bronze in sodium chloride solution has been studied ^tentiostatically at five temperatures in the range 293-313K.The corrosion potential shifted to more negative values with increasing temperature. The corrosion current density increased with increasing temperature. Values of Tal’el slopes and the transfer coefficients indicated hydrogen evolution reaction to occur at the cathode and mainly the dissolution at the anode.Benzotriazole (BTA) had an inhibiting effect ??? the corrosion of the Al-bronze in deaerated NaCl solution at a concentration (1*10’?- IxlO‘1) mol dm’^ over the temperature range 293-313K. Values of the protection efficiency and kinetics parameters were obtained from the corrosion current densities. ’I’he results indicated that corrosion reaction on Al-bronze occurred on surface sites having different energies of activation.